Infants Autonomic Cardio- Respiratory Responses to Nurturing Stroking Touch Delivered by the Mother or the Father - Van Puyvelde, Martine; Collette, Laetitia; Gorissen, An-Sofie; Pattyn, Nathalie; McGlone, Francis (Frontiers in Physiology, 2019)
The building of physiological self-regulation during bonding is a crucial developmental process based on early cardio-respiratory maturation. The mother’s role as a facilitator of this physiological maturation has been evidenced and recognized in many respects. Research in fathers, however, remains sparse and fathers may persist in the idea that infant bonding is a physiological behavior reserved for a mother’s maternal instinct. In the current study we compared the impact of paternal and maternal nurturing stroking touch on infants’ physiological self-regulation in terms of respiratory sinus arrhythmia (RSA). We compared the impact of a 3-min stroking period (STROKING) with a pre-baseline (PRE-STROKING) and post-baseline (POST-STROKING) of 25 mothers and 25 fathers (unrelated to one another) on their infants, aged 4-16 weeks. We registered infant electrocardiogram (ECG) and respiration to calculate infant RR-interval (RRI), respiration rate (fR) and (respiratory corrected) RSA (RSAcorr). Based on video-recordings, we analyzed the stroking speed. Infants’ RSAcorr significantly increased during and after stroking, no matter whether touch was delivered by fathers or mothers. This effect was mediated by both heart rate (HR) and respiration. However, respiratory mediation occurred later when delivered by fathers than by mothers. Both mothers’ and fathers’ stroking speed occurred within the optimal stimulation range of c-tactile (CT) afferents, a particular class of cutaneous unmyelinated, low-threshold mechano-sensitive nerves hypothesized to be involved in interpersonal bonding. The discussion builds on the idea to mitigate fathers’ doubts about their paternal capabilities and proposes a research agenda regarding the further examination of the role of nurturing touch and its underlying mechanisms within the development of infants’ physiological self-regulation. Finally, the importance of respiratory measurements in infant physiological research is emphasized.